The Degree to Which Islamic Education Teachers Possess The Competencies of Using Modern Educational Platforms from The Point of View of Government School Principals in The Koura District Education Directorate - Rababa, Nedal Mohammed Ahmad (Journal of Educational and Psychological Sciences, 2022)
This Study aimed to identify The degree to which Islamic Education teachers possess the competencies of using modern educational platforms from the point of view of Government school principals in the Koura district education directorate, the researcher used the descriptive approaches, study Sample consisted from (91) female and male principals, chosen intentionally, to collect data Questioner used, which consisted (24) paragraph divided to three-sector, the result of SPSS analysis shown that The degree to which Islamic Education teachers possess the competencies of using modern educational platforms from the point of view of Government school principals in the Koura district education directorate was moderated, the finding also showed there is no statistically significant differences at (α≤0.05) refers to principal sex (male and female) in addition there were statistically significant differences between the principals years of experience in favor of (less than 10 years). In light of these results, the study recommended a set of recommendations, the most important of which are spreading the culture of e-learning and the importance of employing educational platforms in education and modern technological technologies.
Keywords: Competencies of Using Modern Educational Platforms; Islamic Education Teachers; Government School Principals; The Koura District Education Directorate